WAKAF BERBASIS MASJID UNTUK MENGURANGI ANGKA KEMISKINAN (UINSI Samarinda, 2013)
An Indonesian State ironic thing is rich with its natural resources on the one hand, but on the other side to reach 29 million more people living in poverty, and the majority are Muslims. On the other hand Muslims have economic resource potential to alleviate poverty is waqf. However, due to the narrow understanding of the waqf and fanatics cling to one school of opinion priests, and weakness Nazhir endowments should be responsible for the existence, eternity and utilization, it functions more endowments for religious purposes mahdhah, while socio-economic functions that can improve economy people are not excavated. With the birth UU/41/2004 about endowments, especially cash waqf or waqf cash that may have been set by the MUI dated May 11, 2002, where the cash waqf has the flexibility of its use, is expected waqf property can be managed professionally, with modern management, transparent and accountable . And by making the mosque as basic management, it would be able to prosper materially worshipers surrounding mentally and spiritually, and to help the Government to reduce poverty in the country of Indonesia.